2013
DOI: 10.4028/www.scientific.net/amm.405-408.1928
|View full text |Cite
|
Sign up to set email alerts
|

Research on Proportioning Design of Tourmaline Modified Asphalt Mixture

Abstract: In order to study the effect of tourmaline on asphalt mixture design indexes, the optimal asphalt content of modified asphalt mixture with different contents of tourmaline were determined through Marshall Test, and the variation of optimal asphalt content caused by tourmaline was analyzed. The effect of tourmaline on density, porosity, VMA, VFA, stability, flow value were studied. Under the guidance of surface theory and mortar theory respectively, the Marshall Volume indicators of tourmaline modified asphalt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…From the literature, the addition of TP has been proved to be an efficient way to enhance the performance of asphalt binders and asphalt mixtures, respectively. Based on chemical composition analysis, the colloidal structure of the asphalt binder remains as a sol-gel type with TP [30]. From the study [30], the OAC of the three different modified asphalt mixtures with TP dosages of 14%, 17%, and 20% were 5.45%, 5.53% and 5.60% respectively.…”
Section: Literature Review and Study Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature, the addition of TP has been proved to be an efficient way to enhance the performance of asphalt binders and asphalt mixtures, respectively. Based on chemical composition analysis, the colloidal structure of the asphalt binder remains as a sol-gel type with TP [30]. From the study [30], the OAC of the three different modified asphalt mixtures with TP dosages of 14%, 17%, and 20% were 5.45%, 5.53% and 5.60% respectively.…”
Section: Literature Review and Study Motivationmentioning
confidence: 99%
“…Based on chemical composition analysis, the colloidal structure of the asphalt binder remains as a sol-gel type with TP [30]. From the study [30], the OAC of the three different modified asphalt mixtures with TP dosages of 14%, 17%, and 20% were 5.45%, 5.53% and 5.60% respectively. Hu et al [31] observed the aging properties of the modified asphalt binder with TP after the thin film oven test (RTFOT).…”
Section: Literature Review and Study Motivationmentioning
confidence: 99%
“…Based on the aforementioned principle, Mckinley et al [15], Navid and Pilon [16], and Nguyen et al [17] used TAP for absorbing waste heat. Although Wang et al [18][19][20][21][22] have conducted detailed studies with respect to the usage of TAP as a construction material, it is not widely used in highway construction at present. TAP is used as an inorganic asphalt modifier to prepare modified asphalt that exhibits flame-retardant and smoke-suppression properties.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of calcium carbide modifier on the performances of pavement was emphatically studied [23,24]. The effects of tourmaline on asphalt density, dynamic stability, and flow value were analyzed, and the micro-mechanism of tourmaline modified asphalt was also studied [25][26][27][28]. Organic tourmaline exhibits excellent storage stability due to its reduced surface polarity, which pioneer a new way for the development of mineral and copolymer composites [29].…”
mentioning
confidence: 99%